Kerajaan Allah Sebagai Puncak Prioritas Hidup Orang Percaya Menurut Matius 6:33 - Marniwati Gulo; Hendi Hendi (Sekolah Tinggi Teologi Arastamar Bengkulu, 2022)
The meaning of the kingdom of God is often discussed by scholars of theology who reveal that the kingdom of God is something that will come or is happening now. This article provides an understanding for readers that knowing the Kingdom of God as a believer's life priority based on the Gospel of Matthew 6:33 is not something mystical. The kingdom of God can only be known, known, and obtained by knowing God in Christ as its foundation. This study uses the exegesis method with a word analysis approach from the original text, which is to find the spiritual meaning behind the original text. The results of this study found that the kingdom of God is the totality of the lives of believers who do not only focus on physical needs that cause more worry. So that this article provides an understanding that changes the mindset of believers about the kingdom of God in today's world, namely living to seek God and seeking true justice is to put on Christ.